The Effectiveness of Educational Games in Enhancing English Vocabulary for Beginners - Kurniawan, Lalu Deni; Usuluddin, Usuluddin; Maysuroh, Siti; Prasetyaningrum, Ari (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze the effectiveness of educational games in improving English vocabulary for beginners. This research explores the use of educational games in the context of learning English for beginners, and investigates the impact of these games on vocabulary acquisition and retention. This research uses a pre-experimental research design with a one-group pretest-posttest approach. The participants in this research were 19 teenagers who were members of the Sutenegere study group. Data was collected through pre-tests and post-tests. The data were analyzed by using descriptive statistics and paired sample T-test to test the hypothesis. It was performed using SPSS 2022 for windows. The result shows that the mean score of the pre-test was 57.89 and the mean score of the post-test was 64.47. It concluded that the use of educational games significantly increased beginner students' English vocabulary. This research provides practical contributions for teachers in choosing effective learning media and provides guidance for educational game developers. In addition, it is hoped that this research can become a reference for further studies related to vocabulary achievement in language learning.